Moss, C.R. (2019). Divine Bodies. Resurrecting Perfection in the New Testament and Early Christianity - Martínez Maza, Clelia (ARYS. Antigüedad: Religiones y Sociedades, 2020)
MOSS, CANDIDA R. (2019). Divine Bodies. Resurrecting Perfection in the New Testament and Early Chistianity. New Haven – London: Yale University Press. 208 pp., 38,38€ [ISBN 978-0-3001-7976-7] [Book review]